Per una nuova edizione critica dei trattati politici alfieriani - Lucia Bachelet (Prassi Ecdotiche della Modernità Letteraria, 2018)
The contribution was proposed for the first time at the conference "Vittorio Alfieri: éditer, commenter, traduire" (Paris, 16-17 February 2018). The report from this conference is published in this issue of PEML: https://riviste.unimi.it/index.php/PEML/article/view/10451